FRI0591 Risk factors for disease relapse in IGG4-related disease following glucocorticoids treatment. (15th June 2017) - Sasaki, T; Akiyama, M; Kaneko, Y; Yasuoka, H; Suzuki, K; Yamaoka, K; Takeuchi, T
Abstract : Background: IgG4-related disease (IgG4-RD) is a fibroinflammatory disease characterized by elevated serum IgG4 and infiltration of IgG4 + plasma cells at affected sites. The patients with IgG4-RD respond well to glucocorticoids (GCs), but one-third of the patients experience disease relapse during tapering of GCs (1). The risk factors for disease relapse following treatment are unclear. Objectives: The aim of this study was to identify the risk factors of disease relapse following reduction of GCs therapy. Methods: Consecutive, newly diagnosed patients with IgG4-RD who were followed over 6 months after treatment with GCs in our department were enrolled. The patients were divided into two groups according to the presence or absence of disease relapse. Disease relapse was defined as the appearance of new lesions or the re-enlargement of involved organs that required dose-increase of GCs. Patient characteristics and laboratory findings at diagnosis were compared and receiver operating characteristic curve analysis was performed to identify the relevant predictive factors of disease relapse. Results: A total of 34 patients were included and all patients were treated with GCs alone as initial treatment. Ten patients (29.4%) experienced relapses during GCs dose tapering which was at 16.0 months (median) after GCs initiation. No difference was found in age, sex, body weight, and disease duration between the two groups. The observation periods and the initial/last GCs dose were also not different. However, serum IgG4 (939 vs 450 mg/dl, p=0.008), serum IgG4/IgG ratio (0.35 vs 0.24 p=0.046), soluble IL-2 receptor (907 vs 677 U/ml, p=0.032) and number of organ involvement (4.3 vs 3.0, p=0.028) were significantly higher in patients with relapse than those without, while the level of IgA (135 vs 205 mg/dl, p=0.015) and IgM (60 vs 91 mg/dl, p=0.038) were significantly lower in the patients with relapse. IgG4 decreased to a comparable level in both groups after GCs treatment (200 vs 91 mg/dl, p=0.124), but increased in the relapse group afterward (387 vs 115 mg/dl at last observation, p=0.048). The predictive values (sensitivity, specificity) at IgG4-RD diagnosis for relapse were as follows; serum IgG4 570 mg/dl (90.0%, 75.0%), IgG4/IgG 0.31 (70.0%, 79.2%), soluble IL-2 receptor 470 IU/ml (100.0%, 54.5%), the number of affected organs of four (80.0%, 70.8%), IgA 100 mg/dl (50.0%, 100.0%) and IgM 60 mg/dl (80.0%, 75.0%) (Figure 1 ). Conclusions: Higher serum IgG4, soluble IL-2 receptor, and the number of affected organs and lower levels of serum IgA and IgM at baseline indicate the higher likelihood of disease relapse following GCs therapy in patients with IgG4-RD. References: Brito-Zerόn P, Kostov B, Bosch X, Acar-Denizli N, Ramos-Casals M, Stone JH. Therapeutic approach to IgG4-related disease: A systematic review. Medicine (Baltimore). 2016;95:e4002. Acknowledgements: We sincerely thank all the physicians and others caring for the patients enrolled in this study. Disclosure of Interest: None declared